ANALYSIS OF STOCHASTIC INFLATION IN THE INTERACTION OF SUPPLY AND DEMAND REGARDING THE ASPECT OF DINAMIC CAUSALITY - Butautas, Dainius (Ekonomika, 2011)
Systematic analysis of the development of understanding the causes of inflation, taking supply and demand conditions as the central axis, offers a deeper insight into the inflation process and its essence. It is obvious that the long-term inflation impacting human, productive and financial resources can in no way be justified by extremely short-term benefits to a country’s budget or to monopolistic structures. Analysis of the literature clarifies and confirms the fact that in order for inflation to occur and significantly accelerate, the growth of demand factors must exceed that of supply factors during several years. The research shows that the policy of encouraging the demand, and thus a significant and long-lived inflation, is possible only in non-competitive oligopolistic economies marked by corruption and provoking emigration. On the other hand, adjustment of demand instruments to changes in supply is rather a result of fair competition. Interest rate change as an independent factor is shown to be important for the inflation process, especially for deflation, and therefore for the economy. Moreover, it is not completely clear whether delayed is the cause of inflation or its result, but it is obvious that the negative impact of delayed demand, as delayed human and social well-being, results in weaker supply and thereby also in higher poverty and inflation, all of them encouraging a more thorough examination of this problem. Analysis of the phenomenon of inflation over a historic period provides a realistic picture of this problem and shows the ways how to solve it.